PENGARUH LIKUIDITAS, EFISIENSI, DAN UKURAN BANK TERHADAP PROFITABILITAS - Yuniari, Ni Putu; Badjra, Ida Bagus (E-Jurnal Manajemen; Vol 8 No 6 (2019)DO - 10.24843/EJMUNUD.2019.v08.i06.p08, 2019)
Profitability is the ability of a company to earn a profit or measure the effectiveness of management of a company. The profitability ratio used in this study is Return On Assets (ROA). This research was conducted with the aim to determine the effect of liquidity, efficiency and bank size on profitability policies in state-owned commercial banks and foreign banks in Indonesia. The method used to determine the sample is a saturated sample, during the period 2013-2017. Data collection is done by the method of non-participant observation. The data analysis technique used in this study is multiple linear regression. The results showed that liquidity has a significant positive effect on profitability, efficiency has a negative and significant effect on profitability, bank size has a positive and significant effect on profitability and there are differences in profitability between state-owned commercial banks and foreign banks in Indonesia. Keywords : profitability, likuidity, efficiency,  bank size